Rekonstruksi Penyelesaian Sengketa Tanah Keluarga dalam Perspektif Hukum Agraria dan Hukum Islam - Titi Sulastry S; Helda Yusdiana L; Zulfiana Abubakar; Nurjannah Nurjannah; Hendra B; Nurradiyah Sarip (JPPI (Jurnal Pendidikan Islam Pendekatan Interdisipliner), 2025)
Inherited land disputes are a common legal issue within families due to the high economic, social, and emotional value of land. Conflicts typically arise when land inherited from parents has not been clearly divided, ownership documents are incomplete, one heir unilaterally controls the land, or there are differences in understanding between state law, customary law, and Islamic law. This article aims to analyze the resolution of inherited land disputes through the perspectives of agrarian law and Islamic law. This research uses a normative juridical method with a statutory, conceptual, and simple case study approach. The primary legal materials used include the Basic Agrarian Law, the Government Regulation on Land Registration, the Compilation of Islamic Law, the Religious Courts Law, and court mediation regulations. The study results indicate that the resolution of inherited land disputes should prioritize deliberation and mediation because these two mechanisms are more effective in maintaining family relationships. However, if reconciliation cannot be achieved, court proceedings are still necessary to provide legal certainty regarding the status of heirs, land objects, and the distribution of rights. From an Islamic legal perspective, the resolution of inheritance disputes must be based on justice, honesty, transparency, and the prohibition of unjustly seizing the rights of other heirs